Long-term Cd remediation mechanisms and potential risks in soil with biochar application under dry-wet cycling at different soil moisture levels - Shuang Huang; Zhuowen Meng; Jingwei Wu; Lei Xin; Qin Zhao (Agricultural Water Management)
Dry-wet cycling and soil moisture are key factors affecting cadmium (Cd) remediation in soils by biochar; however, their long-term effects on the transport of Cd between soil and biochar, Cd fraction distribution, and Cd potential risks are still unclear. To reveal the long-term Cd remediation mechanisms and potential risks in soil under biochar treatment, 180 days of artificial dry-wet cycling was conducted at four soil moisture levels (40 % θs, 60 % θs, 80 % θs, and 100 % θs; θs, saturated water content, W/W) based on local meteorological data to simulate 30 years of natural dry-wet processes. The results showed that Cd adsorbed by biochar in soils during long-term ageing first underwent rapid adsorption (over 0–5 years of simulated ageing), then equilibrium stabilization (over 5–20 years of simulated ageing), and finally slight re-released (over 20–30 years of simulated ageing). Compared with the total Cd adsorbed by biochar in the 20th year of simulated ageing, Cd adsorption by biochar accounted for 85.28 %, 14.72 %, and −3.22 % during 0–5, 5–20, and 20–30 years of simulated ageing, respectively, in the soil at 100 % θs. Similarly, the available Cd slightly increased in 20–30 years of simulated ageing. The greater the soil moisture was, the more effective the adsorption and immobilization of Cd by biochar. At the 20th year of simulated ageing, the Cd adsorption by biochar at 100 % θs was 1.51 times that at 40 % θs; the available Cd in the soil with biochar at 100 % θs was 0.91 times that at 40 % θs. The contribution of nonmineral components in biochar to Cd adsorption was greater in 0–1 years of the simulation, but the contribution of mineral components dominated and slightly decreased during 1–30 years of the simulation. This study highlighted that biochar was fairly effective in the long-term remediation of Cd in contaminated soils, but there was some risk of Cd activation in the later stages due to the ageing of biochar. Agricultural irrigation management has a significant effect on the long-term effectiveness of biochar remediation of Cd pollution. To prevent Cd reactivation, a high field moisture level is recommended, and excessive dry-wet cycling should be avoided through water management practices such as frequent irrigation with small amounts of water.